Parents perceptions to wards community-based rehabilitation programme at Felda Bukit Goh Health Centre, Kuantan, Pahang, 1995 - Fatimah A. Majid,; Hanafiah Mohd. Salleh, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study regarding the status of parents' perceptions towards community-based rehabilitation programme was carried out at Bukit Goh H ealth Centre, Kuantan, Pahang. All the 23 parents and their disabled child who have registered for this programme from February 1994 to December 1994 were taken as study samples. It is important to have parents with positive perceptions who will give continous commitment, active participation and will ensure the survival of the programme. A guided questionnaire was used to measure parents perceptions and a group of selected toys and Denver Developmental Screening Test were used to measure the current status of childrens' skills development. The study revealed that 78.3% of parents have positive perceptions and 21.7% negative perceptions. No significant differences or relationships were found between parents' perceptions with studied variables. However, there are positive correlations between parents, knowledge, attitudes and motivations with childrens' skills performances and between parents' knowledge with attitudes. Based on these findings, parents' perceptions towards the programmes can be improved indirectly by special emphasis on these positive factors.